2018
DOI: 10.1016/j.bbamem.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Applications of sequence coevolution in membrane protein biochemistry

Abstract: Recently, protein sequence coevolution analysis has matured into a predictive powerhouse for protein structure and function. Direct methods, which use global statistical models of sequence coevolution, have enabled the prediction of membrane and disordered protein structures, protein complex architectures, and the functional effects of mutations in proteins. The field of membrane protein biochemistry and structural biology has embraced these computational techniques, which provide functional and structural inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 173 publications
1
24
0
Order By: Relevance
“…The algorithm reproduces self pairings for 74% of all sequences in the alignment, averaged across 5 replicates, after iteration to convergence. This is on par with accuracy of partner detection for other proteins pairs performed by related algorithms (23,34) and supports the use of our model built from natural sequences. When the EC1/EC4 and EC2/EC3 interactions were paired in isolation, we found that the accuracy of matching was less than when the whole interface was used, indicating that both interfaces act in combination to achieve full specificity of the interface.…”
Section: Model Parameters Reveal Biochemical Interactions Underlying supporting
confidence: 78%
See 1 more Smart Citation
“…The algorithm reproduces self pairings for 74% of all sequences in the alignment, averaged across 5 replicates, after iteration to convergence. This is on par with accuracy of partner detection for other proteins pairs performed by related algorithms (23,34) and supports the use of our model built from natural sequences. When the EC1/EC4 and EC2/EC3 interactions were paired in isolation, we found that the accuracy of matching was less than when the whole interface was used, indicating that both interfaces act in combination to achieve full specificity of the interface.…”
Section: Model Parameters Reveal Biochemical Interactions Underlying supporting
confidence: 78%
“…Furthermore, simulations can improve consistency when defining interface residues in a protein family. Computational methods based on residue coevolution have been useful in understanding the structure of Pcdhs, predicting the EC1/EC4 interaction and that the trans dimer architecture exists in nonclustered Pcdhs, both findings later confirmed experimentally (15,16,18,34). Coevolving residue pairs identify interprotein contacts (22,23) but can correspond to positions only in contact in certain conformations (35)(36)(37).…”
Section: Structures and MD Show That Pcdh Trans Interfaces Sample Amentioning
confidence: 88%
“…Computational methods based on residue coevolution predicted the EC1/EC4 interaction and established that the trans dimer architecture would be found in non-clustered Pcdhs, both findings later confirmed experimentally (14,15,18,29). Sequence coevolution methods for protein-protein interface determination are typically benchmarked by comparing highly coevolving residue pairs that are not due to intramolecular structural features to their inter-residue distances in experimentally-determined structures (30,31).…”
Section: Highly Coevolving Residue Pairs Are Frequently In Contact Inmentioning
confidence: 84%
“…The scale of our sequence alignments allowed us to take a closer look at the functional relevance of the PSM in ABC exporters through sequence coevolution analysis. Many predictive techniques for classifying the structural and functional properties of specific sites through multisequence analysis have emerged in recent years [34]. The Evolutionary Trace method is one such approach that is particularly powerful because it can infer likely functionally important features from phylogenetic relations and information content through evolution of a family [35].…”
Section: Evolutionary Contact Predictions Show the Psm Connects Nbds mentioning
confidence: 99%